Factors affecting educational achievement of Tongans in Auckland : a thesis submitted in partial fulfillment of the requirements for the degree of Master of Educational Administration, Department of Education, Massey University, 1997 - Mafi, Maliumoeao (Massey University, 1997)
Underachievement in New Zealand secondary schools has been a problem for Pacific Island people for a long time and unemployment over the years is testimony to the presence of underachievement. (Apart from Hawk and Hill's (1996) study, limited research has addressed this problem). Underachievement is closely associated with a person's socio-economic status and ethnic background. It has been a stigma that has been associated with Pacific Island and Maori people in New Zealand for a long time. Their children's academic performance in School Certificate and Bursary exams throughout the years has confirmed that Tongan students' achievement is below that of other ethnic groups in New Zealand. [From Introduction]
Keywords: Auckland New Zealand Tongans; Education (Secondary); Academic achievement